Evaluation of Nurses’ Attitudes towards Patients’ End of life in Diyala Governorate - ahmeed, shihab (Iraqi National Journal of Nursing Specialties, 2022)
Abstract: Objectives: To assess nurses’ attitude toward end of life phase. To find out relationships between nurses attitude and socio demographic data (age, gender, level of education, years of experience). Methodology: A descriptive cross-sectional study design is carried out to assess the attitude on nurses concerning patient at the end of life phase at critical care units, from the period of (1nd November 2021) to (1th February 2022). A probability sample random sampling technique used. Then, the number of participants in Baquba Teaching Hospital and general al khalis hospital were determined by using randomly selected. simple Total of (100) nurses working at critical care units through the time of the study period and the study criteria and agree to participate. Pilot study were excluded ten nurses from the study. the result of co-relation co efficient were (79%).The content validity of the questioner is obtained by panel of (14) experts. inferential statistics and Descriptive were used to analytic the results of the study using the Statistical Package of Social Sciences (SPSS) version 25 and Microsoft Excel (2016). Results: study results of this showed the level of attitude nurse’s toward End of life care together with nurses working in diyala city in Iraq were (poor 0%, fair 51%, and good49%). There is no significant difference between nurses’ attitude toward care of the dying patient (number of training course, area of employment). Conclusions: nurses have moderate level of attitude, and there is no significant difference between nurses’ attitude toward care of the dying patient (number of training course, area of employment). Recommendations: The recommended of study is necessity of evolving Education or training that can enhance nurses behavior toward End of life care. investigate relationship amonng religion and spiritual of nurses and their attitude toward end-of-life care.